2015
DOI: 10.1183/09031936.00012415
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to identify sputum eosinophilia in different adult asthma phenotypes

Abstract: Several biomarkers have been used to assess sputum eosinophilia in asthma. It has been suggested that the diagnostic accuracy of these biomarkers might differ between asthma phenotypes. We investigated the accuracy of biomarkers in detecting sputum eosinophilia (⩾3%) in different adult asthma phenotypes.Levels of eosinophils in blood and sputum, exhaled nitric oxide fraction (FeNO) and total immunoglobulin (Ig)E from 336 adult patients, enrolled in three prospective observational clinical trials and recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 33 publications
6
120
0
4
Order By: Relevance
“…Unfortunately, the results of these studies are not fully conclusive. One study did not find an improvement in accuracy when combining blood eosinophils, FeNO, and periostin as compared to one of the single biomarkers [46], whereas another study did find a small enhancement in accuracy when combining FeNO and blood eosinophils [50]. Adding IgE to these models did not lead to any improvement of the results.…”
Section: Combinations Of Blood Eosinophils Feno Periostin and Igementioning
confidence: 95%
See 4 more Smart Citations
“…Unfortunately, the results of these studies are not fully conclusive. One study did not find an improvement in accuracy when combining blood eosinophils, FeNO, and periostin as compared to one of the single biomarkers [46], whereas another study did find a small enhancement in accuracy when combining FeNO and blood eosinophils [50]. Adding IgE to these models did not lead to any improvement of the results.…”
Section: Combinations Of Blood Eosinophils Feno Periostin and Igementioning
confidence: 95%
“…From these results, the authors concluded that using a cutoff of 0.45 × 10 9 /L or higher for blood eosinophilia could safely predict airway eosinophilia. Also other studies reported that a blood eosinophil threshold ≥0.4 × 10 9 /L could predict sputum eosinophilia with high probability [8,50]. Westerhof et al not only found a specificity of 95% for blood eosinophils ≥0.41 × 10 9 /L to rule in, but also a sensitivity of 96% for ≤0.09 × 10 9 /L eosinophils to rule out sputum eosinophilia [50].…”
Section: Cutoff Points For Blood Eosinophils Feno Periostin and Igementioning
confidence: 97%
See 3 more Smart Citations